2010
DOI: 10.1177/1557988310375606
|View full text |Cite
|
Sign up to set email alerts
|

Having a Primary Care Provider and Receipt of Recommended Preventive Care Among Men in New York City

Abstract: To assess the role of having a primary care provider (PCP) in men's up-to-date receipt of recommended preventive services (colonoscopy, pneumococcal and seasonal influenza vaccination, cholesterol and blood pressure screenings), data from the 2005 and 2006 New York City Community Health Surveys (N = 3,728 [2006], 2,810 [2005]) were analyzed. PCP prevalence and men's uptake of each service, overall and by age, race/ethnicity, education, income, insurance status, marital status, and nativity, were evaluated. Aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 32 publications
3
8
0
Order By: Relevance
“…Earlier studies have reported the importance of a health care providers’ recommendation for uptake of the influenza vaccine [9; 10], and this was observed here. Of note, low interest in getting the vaccine among those who saw their health care providers during influenza season was offset in part by a provider recommending that the patient take the vaccine.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Earlier studies have reported the importance of a health care providers’ recommendation for uptake of the influenza vaccine [9; 10], and this was observed here. Of note, low interest in getting the vaccine among those who saw their health care providers during influenza season was offset in part by a provider recommending that the patient take the vaccine.…”
Section: Discussionsupporting
confidence: 75%
“…Factors that have been cited for this disparity include lack of interest in getting the vaccine [2], attitudes such as mistrust in government [2; 6], and reduced or lack of access, whether it be related to vaccine supply, cost or limited skills in navigating health care settings [5; 7; 8]. Recommendation from a health care provider can contribute to accepting and receiving immunizations [912], provided that the person has access to a clinician during the period that vaccine is available.…”
Section: Introductionmentioning
confidence: 99%
“…More frequent medical visits also provide more opportunities for providers to discuss and promote CRC screening, and primary care provider recommendations are an important factor in patients attending a screening colonoscopy. (4, 19, 21, 23, 24)…”
Section: Discussionmentioning
confidence: 99%
“…From a broader perspective, Jasek (2011) identified that having a regular PHC provider garnered preventative services regardless of insurance status and ethnicity—yet those connections can be especially challenging to make with male patients. For example, in Canada males 20 to 64 years of age are far more likely than females to not have a regular doctor ( Statistics Canada, 2015 ).…”
Section: Episodic Medical Care and Men’s Healthmentioning
confidence: 99%